Respuesta :
Answer:
4 + 7x – 2
Step-by-step explanation:
Equivalent Expressions
Let's find out which expressions are equivalent by simplifying them. One of the expressions should be not equivalent to the other three.
Simplifying
[tex]2x + 2+ 2x + 3x -8=7x-6[/tex]
Now for the second expression
[tex]4 + 7x -2=7x+2[/tex]
The third expression simplifies to
[tex]-2 + 5x + 2x - 4=7x-6[/tex]
Finally, this is the simplification for the expression
[tex]8x - x - 6=7x-6[/tex]
As seen, the only expression not equivalent to the other three is 4 + 7x – 2